Digitalizaçao de acervos fotográficos públicos e seus reflexos institucionais e sociais: tecnologia e consciência no universo digital - Silva, Rubens Ribeiro Gonçalves da (2002)
The object of investigation of this study are projects or activities for digitalization of public photographic collections and how it affects institution/user relations. New concepts and practices were identified as well as its implications in photographic documentation access. The theoretical investigation was associated to an empirical action developed in sixteen public institutions repository of photographic collections related to art, culture, and history, all of them at Rio de Janeiro City, Brazil and with its users, allowing us to identify needs and demands, and ways to satisfy them. We understand information as a process that makes possible an expansion of consciousness; the contents of digital photographic collections are a representative dimension of this possibility of consciousness expansion. This study proposes a model to make digital versions of these collections available on the world wide web